Usabilidade de softwares utilizados para visualização e análise de modelos digitais ortodônticos - Rocha, Matheus Felter (2019)
Orthodontic digital models have advantages over physical plaster models. However, for them to be replaced, it is important that digital models provide all the necessary functionality to the orthodontist, be reliable, accessible in cost and easy to handle. The objective of this work was to evaluate the usability of software provided free of charge and that allow visualization and analysis of digital orthodontic models. Eighty students from post-graduate courses in Orthodontics were asked to perform pre-defined tasks in a digital model through 3D Viewer ® and 3D-Tool ® software. The success in the accomplishment of the tasks and the time spent were evaluated. Finally, each participant answered a questionnaire to express their satisfaction regarding specific aspects of the use of each software. Sixty-four (80%) participants were able to manipulate the model in 3D Viewer ®, while sixty-nine (86%) did so in the 3D-Tool ®. On the other hand, only 52.5% were able to find the linear measurement tool in 3D Viewer ® and only 33.7% in the 3D-Tool ®. The time spent to perform the measurements did not present significant differences, being around two minutes in each software. The two software were evaluated, on average, as "not very good" in several criteria related to the satisfaction of use by the participants who experienced them, there being scope for optimization of their interfaces by the manufacturers and problems to be considered by the clinician who wishes to work with one of them for the visualization and analysis of orthodontic digital models.